A worker in a worker's state (Penguin, in association with New Left Review, 1981)
Also contains a note about the author and a transcript of the authors trial. - First publ. as Stücklohn by Rotbuch Verlag, Berlin 1975. - This ed. publ. in Pelican Books 1977.